Completely bounded polynomials between operator spaces - Dineen, Seán; Radu, Cristina (Mathematica Scandinavica, 2010)
In this article we introduce the concept of a completely bounded polynomial between operator spaces, prove some basic properties and determine the operator structure of the space of diagonal polynomials on the more important operator Hilbert spaces.